2017
DOI: 10.3390/ijms18122628
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Intrauterine Environment and Cardiac miRNA Expression

Abstract: Placental insufficiency, high altitude pregnancies, maternal obesity/diabetes, maternal undernutrition and stress can result in a poor setting for growth of the developing fetus. These adverse intrauterine environments result in physiological changes to the developing heart that impact how the heart will function in postnatal life. The intrauterine environment plays a key role in the complex interplay between genes and the epigenetic mechanisms that regulate their expression. In this review we describe how an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 142 publications
(171 reference statements)
0
24
0
Order By: Relevance
“…Studies from several other laboratories have also demonstrated that miRNAs are associated with developmental programming of various organs (Zucchi et al 2013, Casas-Agustench et al 2015. The organs and tissues investigated include heart (Yan & Jiao 2016, Lock et al 2017), brain (Petri et al 2014) and several endocrine glands (pancreas, ovary, testes, hypothalamus and pituitary) (Kredo-Russo et al 2012, Voglova et al 2016. Of note, exposure to environmental toxins during human pregnancy affects miRNA expression in cord blood, which lead to increased disease susceptibility in offspring (Rager et al 2014, Gillet et al 2016).…”
Section: Mirna and Dohadmentioning
confidence: 99%
“…Studies from several other laboratories have also demonstrated that miRNAs are associated with developmental programming of various organs (Zucchi et al 2013, Casas-Agustench et al 2015. The organs and tissues investigated include heart (Yan & Jiao 2016, Lock et al 2017), brain (Petri et al 2014) and several endocrine glands (pancreas, ovary, testes, hypothalamus and pituitary) (Kredo-Russo et al 2012, Voglova et al 2016. Of note, exposure to environmental toxins during human pregnancy affects miRNA expression in cord blood, which lead to increased disease susceptibility in offspring (Rager et al 2014, Gillet et al 2016).…”
Section: Mirna and Dohadmentioning
confidence: 99%
“…This is, however, unlikely to mirror the advantages seen in pulmonary development. Intrauterine growth restriction has been extensively studied and undernutrition can result in maturational changes in the cardiac myocytes,62 this does not however translate into a clinical functional advantage 63. Furthermore, premature maturation may diminish the total myocyte count into adult life 44.…”
Section: Discussionmentioning
confidence: 99%
“…2011). Premature exit from the cell cycle in fetal development can be caused by adverse changes to the intrauterine environment, resulting in a less structurally complete and less functional organ at birth and throughout postnatal life (Lock et al . 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of non‐coding RNAs, such as miRNAs, plays an important role in the epigenetic machinery and is vital for normal tissue development and function (Lock et al . 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation